Illegal bowling actions contribute to performance in cricket finger‐spin bowlers. (27th February 2018) - Spratford, Wayne; Elliott, Bruce; Portus, Marc; Brown, Nicholas; Alderson, Jacqueline
Abstract : With advances in technology, scientists are now able to more accurately measure elbow displacement changes during the cricket bowling action. This has led to the realization that the majority of bowlers undergo some degree of elbow extension during the forward swing phase of bowling. Consequently, the International Cricket Council were obliged to revise the once zero tolerance for elbow extension threshold to a 15° range. However, it is still not understood if bowling with >15° of elbow extension aids performance or alters other kinematic movements. The purpose of this study was to compare performance and technique measures between legal and illegal finger‐spin bowlers. Data were collected from 48 pathway and elite bowlers using a 22‐camera motion analysis system. Results indicated that the ball velocity and revolutions at ball release of pathway bowlers with illegal actions showed no significant difference and were similar to elite legal bowlers. Technique differences were also identified, with illegal bowlers being more front‐on, forcing a reliance on increased elbow flexion and supination to impart effective ball kinematics at ball release. The performance benefit of greater ball velocity and revolutions is obtained when finger‐spin bowlers deliver the ball with more than the allowable 15° of elbow extension, thus reinforcing the validity of the current bowling laws. To counteract bowling with an illegal action, it is recommended that a more side‐on technique at back foot impact and rotating the trunk through to the point of ball release will assist bowlers in reducing undesirable elbow extension levels.